2018
DOI: 10.22201/ib.20078706e.2018.1.2105
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of wild drone congregations of the stingless bee Scaptotrigona mexicana (Hymenoptera: Apidae) reveals a high number of colonies in a natural protected area in Southern Mexico

Abstract: Revista Mexicana de Biodiversidad 89 (2018): 226-231Conservación Genetic analysis of wild drone congregations of the stingless bee Scaptotrigona mexicana (Hymenoptera: Apidae) reveals a high number of colonies in a natural protected area in Southern Mexico El análisis genético de congregaciones silvestres de zánganos de la abeja sin aguijón, Scaptotrigona mexicana (Hymenoptera: Apidae) revela un elevado número de colonias en una área natural protegida del sureste de MéxicoAbstract In this study, drone congrega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Despite evidence for the high probability of mating between wild and managed individuals in stingless bees, no study has demonstrated experimentally that new alleles actually enter the genetic pool of managed colonies via the mating of managed queens with wild male stingless bees. We therefore sought to test this hypothesis and chose S. mexicana as our biological model, because it is commonly used in meliponaries, has been extensively investigated (Guzmán Díaz et al, 2004;Sánchez et al, 2016;Sánchez-Guillén et al, 2018), is relatively common as wild colonies in the study area (Ayala, 1999), and has a cultural and economic role in local communities. Moreover, since some stingless bee species once thought to be singly mated, are now known to be multiply mated, we also investigated the mating frequency in S. mexicana.…”
Section: Polyandry and Gene Flow In A Stingless Beementioning
confidence: 99%
“…Despite evidence for the high probability of mating between wild and managed individuals in stingless bees, no study has demonstrated experimentally that new alleles actually enter the genetic pool of managed colonies via the mating of managed queens with wild male stingless bees. We therefore sought to test this hypothesis and chose S. mexicana as our biological model, because it is commonly used in meliponaries, has been extensively investigated (Guzmán Díaz et al, 2004;Sánchez et al, 2016;Sánchez-Guillén et al, 2018), is relatively common as wild colonies in the study area (Ayala, 1999), and has a cultural and economic role in local communities. Moreover, since some stingless bee species once thought to be singly mated, are now known to be multiply mated, we also investigated the mating frequency in S. mexicana.…”
Section: Polyandry and Gene Flow In A Stingless Beementioning
confidence: 99%